Guru Pendidik Profesional dan Implementasi Kurikulum 2013 - Ni Made Sueni; Alit Sudiarti Desak Nyoman (FAKULTAS PENDIDIKAN BAHASA DAN SENI IKIP SARASWATI, 2022)
Whatever the curriculum, it must be supported by professional teachers. Teachers are as the forefront and the spearhead the curriculum implementation and learning dealing with students directly. In other words, without professional teachers, the change of curriculum will not afford a significant contribution to the quality of learning and graduates. The importance of professional teachers in the successful implementation of 2013 curriculum can be traced in every learning process. The teacher is the determining factor, because what happens in the class is what conducted by the teacher. Therefore, in the implementation of 2013 curriculum, teachers still play important role, both in planning, implementation, and evaluation. Based on that fact, it is important to increase the competence, activity, creativity, quality and professionalism of teachers.